2014
DOI: 10.1097/nor.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Care Coordination for the Intellectually and Developmentally Disabled Adult in the Residential Care Setting

Abstract: The role of the nurse as care coordinator is important in all patient populations, including orthopaedic settings, and is essential in promoting safe patient care for the intellectually and developmentally disabled (I/DD) person living in the residential setting. Care coordination for this population is challenging. Most healthcare providers, as well as nurses, are not familiar with the residential group home setting or with the special needs of this population, especially when presented with orthopaedic chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Many individuals with IDD experience some difficulty both with expressive and receptive communication skills. Several studies reported both expressive and receptive communication challenges experienced by adults with IDD as a barrier to accessing health care (Greenwood, Dreyfus, & Wilkinson, 2014; Kurre, 2014; Nicolaidis et al, 2015; Warfield, Crossman, Delahave, Deer Weerd, & Kuhlthau, 2015; Zerbo, Massolo, Qian, & Croen, 2015). Adults with IDD either had difficulty understanding the information from their provider or were not able to effectively communicate their thoughts, wants, or needs regarding their health or need for health services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many individuals with IDD experience some difficulty both with expressive and receptive communication skills. Several studies reported both expressive and receptive communication challenges experienced by adults with IDD as a barrier to accessing health care (Greenwood, Dreyfus, & Wilkinson, 2014; Kurre, 2014; Nicolaidis et al, 2015; Warfield, Crossman, Delahave, Deer Weerd, & Kuhlthau, 2015; Zerbo, Massolo, Qian, & Croen, 2015). Adults with IDD either had difficulty understanding the information from their provider or were not able to effectively communicate their thoughts, wants, or needs regarding their health or need for health services.…”
Section: Resultsmentioning
confidence: 99%
“…Carroll (2015) found that adults with cerebral palsy (CP) had difficulty with insurance companies approving needed services like physical therapy to maintain function. Kurre (2014) noted the complexities of providers staying up to date with Medicaid and Medicare regulations which affected care access. Adults with ASD identified employment challenges which resulted in poverty and/or difficulty maintaining insurance coverage (Nicolaidis et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Bununla birlikte fiziksel engeli olan bireylerin yaşadığı ortopedik zorluklar da göz önünde bulundurulduğunda, fiziksel olarak engelli bireyler hemşirelik bakım gereksinimi açısından özellikli hasta grubu olarak düşünülmelidir. 14 Araştırma fiziksel engeli olan hastaların hemşirelik bakım davranışı algıları ve bu algıyı etkileyen faktörlerin belirlenmesi amacıyla tanımlayıcı ve kesitsel olarak yapılmıştır.…”
Section: Hemşirelerunclassified